Pulmonary Rehabilitation After Lobectomy On Pulmonary Aspergilloma: Case Report - Andwi Setiawan Kokok; Selly Christina Anggoro; Siti Chandra Widjanantie (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Complete resection of aspergilloma in chronic pulmonary aspergillosis (CPA), may hasseveral health problem after surgery berupa sesak napas, batuk yang tidak efektif.Methods: A case presentation of 45 years old woman, after lobectomy on right upper of lung dueto aspergilloma, with history of cough and haemoptysis for 3 months. Pulmonary Rehabilitation werebreathing retraining exercise (BE), mobilization technique (MT), chest mobility exercise (CM), activecycle breathing technique (ACBT), postural correction exercise (PC) for three weeks.Results: There were dyspnea, peak flow rate (PFR:60-70-60), peak cough flow (PCF: 70-90-60 L/m),and abnormal chest expansion (CE: 2.5 – 3 – 2) cm. After three weeks of Pulmonary Rehabilitation,there were no dyspnea, increased the PCF: 193L/m, and CE: 2.5-4 -3.Conclusion: Pulmonary Rehabilitation programs for three weeks were relieved dyspnea, increasedcough capacity and CEKeywords: Aspergilloma, Lobectomy, Bell’s Palsy, Rehabilitation program, Cough capacity, Chestexpancy